O Brasil na OCDE : análise dos aspectos jurídicos, políticos e econômicos das estratégias de inovação e abertura de mercado no projeto Going Digital - Lima, Daniel Cândido de (2024)
In this study, we propose an analysis of the interactions between Law, Politics and Economy in the context of digital transformation and Brazil's possible accession to the OECD. International trade is recognized as a catalyst for global economic development, with the OECD standing out as a central organization in this scenario of cooperation between sovereign nations. The OECD's Going Digital project is cited as an important strategy to guide the transition to a more sustainable digital economy. The central problem lies in understanding the dynamics between Law, Politics and Economy during this transition, considering the role of technological innovations and the strategies proposed by the OECD. The general objective of this dissertation is to analyze how the interaction between Law, Politics and Economy, mediated by technological innovations and strategies proposed by the OECD in the Going Digital project, influences Brazil's position in the global economic scenario during the economic transition to a technological base. Specific objectives include analyzing Luhmann's Systems Theory as a conceptual framework capable of explaining the complex interactions between the areas studied; examine the impacts of disruptive technologies on practices in Law, Politics and Economics during the transition to a technological base; and evaluate the OECD's strategies in the Going Digital project and their effect on Brazil's position on the global stage. The methodology adopted is dissertation-descriptive with bibliographic and documentary methods, in addition to the systemic approach method based on Luhmann's Systems Theory. The results highlight the relevance of Luhmann's theory for understanding complex interactions between social systems, as well as the impacts of technological innovations on legal, political and economic practices during the transition to a digital economy. Likewise, the results highlight the potential benefits of Brazil's membership in the OECD, such as access to international standards, modernization and competitiveness, in addition to exploring theoretical and practical implications, such as the adaptation of Law to emerging technological issues and the improvement of digital governance in politics. The conclusions point to future research, such as the growing impact of digital transformation on social systems and the more comprehensive analysis of digital governance and legal regulation in the era of the digital economy.